Pengembangan Bahan Ajar Buku Teks Bahasa Arab Berbasis Audio Visual Untuk Siswa Kelas X SMK - Ferdana Sidiq; Sulthan Syahril; Rumadani Sagala; Erlina; Koderi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
Textbooks are teaching materials that are the main element in the ongoing learning. This research and development is based on the gap in the delivery of material in Arabic learning. The purpose of this research is to develop audio-visual-based textbook teaching materials for class X SMK students that are packaged in an attractive, practical and effective way. The development model in this study refers to the Borg and Gall development model. The test subjects of this research product were students of class X SMK Muhammadiyah 2 Kalirejo. The results of this study explain that design and media expert validators give a percentage of the design of textbook teaching materials on the display aspect with a score of 98.43% (very feasible); aspects of use obtained a score of 97.91% (very feasible); and the aspect of Utilization obtained a score of 91.66% (very feasible), while from the material and language expert validators for the Introduction aspect, a score of 100% (very feasible); the content aspect obtained a score of 97.5% (very feasible); Learning aspects obtained a score of 95.83% (very feasible); and the Task/Exercise aspect obtained a score of 92.5 (very feasible); and the results of the posttest of students obtained the average overall score of the three aspects of 94.17% (very feasible). Keywords: Development of Teaching Materials, Textbooks, Audio Visual